PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN KELUARGA, DAN THIN CAPITALIZATION TERHADAP PENGHINDARAN PAJAK - Achmad Tarmizi; Didin Hikmah Perkasa (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
The purpose of this study is to test and analyze the effect of institutional ownership, family ownership, and Thin Capitalization on tax avoidance. This study uses data on manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021, this study uses purposive sampling method. The sample of this study had 6 companies that met the criteria. This study uses a panel data regression analysis method which is a combination of time series and cross data to obtain more informative data. From the regression test results table, it can be stated that Institutional Ownership has a significant positive effect on tax avoidance at the 95% confidence level, family ownership has no effect on avoidance, Thin Capitalization has a significant positive effect on tax avoidance at the 95 confidence level, and Institutional Ownership, Family ownership and Thin Capitalization together have an effect on the dependent variable tax avoidance.